'n kritiese evaluering van die Suid –Afrikaanse diskoersanalise - Jordaan, Gert J. C. (Koers, 1986)
In this article South African Discourse Analysis is looked at critically, especially with regard to the claim to objectivity and scientific verifiability made by the supporters of the method. Four presuppositions which underlie South African Discourse Analysis are discussed. Following that, Discourse Analysis is defined and the relevant steps in the application of the method are outlined - in each instance accompanied by critical remarks. In the final analysis the value of this method is indicated.